Seasonal overview of beef meat quality in a small-scale slaughterhouse. Issue 1 (October 2021) - Vicic, I; Petrovic, M; Stajkovic, S; Cobanović, N; Karabasil, N
Abstract: The objective of this study was to investigate a possible relationship between blood parameters related to animal welfare and defined beef meat quality characteristics during winter and summer seasons in one small-scale slaughterhouse. At exsanguination, blood samples were collected, and serum concentrations for total proteins (TP), albumin and C-reactive protein (CRP) were evaluated. After 24 h of chilling, ultimate pH was measured and meat samples were used for drip loss and cooking loss determination. Dehydration was not observed during seasons, while elevated concentrations of TP accompanied by higher CRP values pointed to summer as a more stressful season. Analysing the meat quality parameters, it was observed that during the two seasons, ultimate pH values were in the range for normal meat acidification, but values for drip and cooking loss were significantly increased during the summer season. In conclusion, CRP could be used as potential biomarker for beef meat quality estimation, in the first instance drip loss and ultimate pH.